The Effect of Principal’s Leadership and Infrastructure Support on Teacher’s Performance - Ulfah, Rezka; Harapan, Edi; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2023)
Leadership is a birth from a protracted process of change in a person rather than a position or title. Teacher performance is always the center of attention because it is one of the factors in improving student achievement, so that teacher performance is always considered and various efforts are made to improve teacher performance. The infrastructure resources that Gunung Raja District schools have to support the educational process are insufficient to assist teachers in their instruction and prevent the development of students’ knowledge and abilities. The researcher is motivated to study